Estrogens regulate the survival and death communication between Sertoli and germ cells: a clue for male infertility? - Alves, Mário Rui Castanheira (2013)
In the last decades estrogens have been regarded as “male hormones” playing an important role controlling male reproductive function. However, the effect of estrogens regulating testicular function and the spermatogenic process it is not fully addressed. Estrogenic actions in target tissues, including testis, are mediated by hormone interaction with the classical estrogens receptors (ER and ER) and also via the membrane G-protein coupled receptor (GPR30/GPER). Ultimately, the estrogens alter the gene expression network in cells and tissues modulating its functioning. Male fertility relies on a successful spermatogenesis, which is dependent from the support of Sertoli cells (SCs), the somatic cells within seminiferous tubules (SeT). Apoptosis is a key event strictly maintaining the appropriate ratio between germ cells and SCs and, thus, it is crucial to maintain the spermatogenic output. It has been suggested that SCs play a crucial role controlling germ cells fate, by secretion of survival and death factors, which act on receptors in germ cells. These include the survival factor desert hedgehog (Dhh), the stem cell factor (SCF) and its receptor the c-kit, as well as the death factors Fas-Ligand (FasL) and Fas-receptor (FasR). It has been shown that estrogens regulate Dhh, SCF, c-kit, FasL and FasR expression in several other tissues. Therefore, we hypothesize that estrogens may influence germ cell survival or death in testicular cells by governing the expression of SCF, c-kit, FasL, FasR. In the present work rat SeT and SCs were cultured in presence or absence of 100nM of 17β-estradiol (E2), and the expression of the aforementioned factors was studied through real-time PCR and Western blot techniques. In addition, in order to start elucidating the molecular mechanisms by which the estrogenic effects are attained, SCs were cultured with E2 0,1nM and with 100nM of each ER specific agonist: G1, DPN and PPT, respectively, agonists for GPER, ERand ER. E2 down-regulated the c-kit expression while increasing expression of its ligand, SCF, both in SeT and SCs. The expression of Fas system, FasR and FasL was also increased in response to E2. No differences were found in Dhh expression between experimental groups. The expression of SCF and FasL in SCs was strongly increased by G1 stimulation indicating the involvement of GPRER. Our results demonstrated that the estrogenic stimulation may modulate germ cell apoptosis in a direct way or through altering germ cell:SCs communication, which could have a profound impact in male fertility, particularly in cases of hyperestrogenism.